Isolation of Additional Bacteriophages with Genomes of Segmented Double-Stranded RNA - Mindich, Leonard (American Society for Microbiology, 1999)
Eight different bacteriophages were isolated from leaves of Pisum sativum, Phaseolus vulgaris, Lycopersicon esculentum, Daucus carota sativum, Raphanus sativum, and Ocimum basilicum. All contain three segments of double-stranded RNA and have genomic-segment sizes that are similar but not identical to those of previously described bacteriophage φ6. All appear to have lipid-containing membranes. The base sequences of some of the viruses are very similar but not identical to those of φ6. Three of the viruses have little or no base sequence identity to φ6. Two of the viruses, φ8 and φ12, contain proteins with a size distribution very different from that of φ6 and do not package genomic segments of φ6. Whereas φ6 attaches to host cells by means of a pilus, several of the new isolates attach directly to the outer membrane. Although the normal hosts of these viruses seem to be pseudomonads, those viruses that attach directly to the outer membrane can establish carrier states in Escherichia coli or Salmonella typhimurium. One of the isolates, φ8, can form plaques on heptoseless strains of S. typhimurium.